If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 + -1x = 22 Reorder the terms: 1 + 4x + -1x = 22 Combine like terms: 4x + -1x = 3x 1 + 3x = 22 Solving 1 + 3x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 22 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 22 + -1 3x = 22 + -1 Combine like terms: 22 + -1 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| x+3=-6 | | x^2+1= | | 12x+7=8x+27 | | n+2m-2n+4m+3n= | | 7x+6(-3x-3)=-25-4 | | 4x+10=-42-9x | | -28-4x=8-8x | | x=-x+30 | | 3x+7=13x-53 | | 2(3x+9)-30=6 | | 12+2n=20 | | (y-7)-(y+7)=9 | | 4x+6=3(x-1) | | 14(x-3)-22x=18solvex | | -10y-3=7 | | 4x-6=3(x-1) | | (15+x)*3=180 | | 22+11=9t+7-6t | | (15+x)*3=185 | | 3x+16-7y=20 | | x+15=180 | | x+15*3=180 | | 3n+8=26 | | y=x^2-4x+1 | | 0=19n | | 2n-7=9 | | -8(4+9s)=7(-2-11s) | | 8x=-5 | | 10+6x-11+7x= | | 4.5(j-4)=1.5(j+4) | | 34-4=5x+23 | | -3p+8=5-(7p+6) |